Analysis of the Optimalization Strategy for the MyHC Platform in Realizing a Digital Employee-Centric Organization at PT XYZ - Angra Firman Felani; Umar Dwi Yulianto (Journal of Research in Social Science and Humanities, 2026)
Digital transformation in the Human Capital Management (HCM) sector has shifted from mere administrative efficiency to an ecosystem centered on the employee experience. PT XYZ, a Maintenance, Repair, and Overhaul (MRO) company, utilizes the MyHC digital platform to bridge the needs of the organization and its employees. However, the main challenge lies in optimizing MyHC to function as an instrument of empowerment, rather than merely a managerial monitoring tool. This study aims to analyze the optimization strategy of the MyHC platform at PT XYZ to realize a Digital Employee-Centric Organization, where the needs and digital experiences of employees become the top priority. This research employs a Systematic Literature Review (SLR) method following the PRISMA protocol, selecting reputable journal articles from the Google Scholar database published within the last three years (2023-2026). The results indicate that platform optimization focuses on four main pillars: (1) improving the accessibility of self-service to reduce bureaucratic barriers, (2) ensuring data transparency to support fairness in career paths and performance evaluations, (3) providing two-way communication channels to strengthen the employee voice, and (4) strengthening the knowledge management ecosystem. In conclusion, the transformation from a transactional system to an empowerment system that embodies employee-centricity requires a strong alignment between data-driven technological capabilities and organizational policies that prioritize human values.